Optimalisasi Digital Marketing untuk Pengembangan Bisnis UKMK Mandala Wahyu Coffee Shop - MS, Mahrinasari; Nurjannah, Ikke; Rohaeni, Dian; Purba, Irvan Eduardo; Ahada F., M. Zakia; Nurazmi, Nadhiya (IKIP PGRI Bojonegoro, 2024)
This research addresses the high coffee consumption in Indonesia and intense competition in the coffee industry in Bandar Lampung. Despite significant potential in digital marketing, only 8% of Micro, Small, and Medium Enterprises (UMKM) practitioners utilize it. Therefore, the community service activity from the University of Lampung aims to support coffee UMKM in Bandar Lampung in adopting digital marketing strategies to enhance sales and compete in the Society 5.0 era. The activity method focuses on sharing knowledge and socializing digital marketing. The situational analysis phase involves on-site visits to understand the business processes. Socialization and discussions present content on business trends, digital marketing, and social media strategies. Follow-up includes encouraging the creation of additional social media accounts and optimizing online presence. Monitoring and evaluation are conducted to measure understanding and implementation of digital marketing practices, as well as monitor sales growth through social media. On December 10, 2023, Community Service Activity was held in Mandala Wahyu Coffe Shop, involving five participants and three stages: discussion, digital branding and marketing training, and evaluation. This training aims to enhance the online presence and global competitiveness of the cafe. It is expected that the applied digital marketing strategy will make operations more efficient, promote the company effectively, and increase customer engagement. The result of this community service activity is encouregement to increase sales and develop the business of UMKM Mandala Wahyu Coffee Shop trough optimizing digital marketing in social media. The method involves situational analysis, socialization, follow-up, and monitoring. The promotion mix strategy is expected to be effective in making operational activities and digital marketing more efficient. With the new digital strategy, UMKM can save time and be more effective in promotions. Penelitian ini membahas tingginya konsumsi kopi di Indonesia dan persaingan ketat industri kopi di Bandar Lampung. Meskipun potensi digital marketing besar, hanya 8% pelaku UMKM yang menggunakannya. Oleh karena itu, kegiatan pengabdian masyarakat dari Universitas Lampung bertujuan mendukung UMKM kopi di Bandar Lampung mengadopsi strategi pemasaran digital untuk meningkatkan penjualan dan bersaing di era Society 5.0. Metode kegiatan fokus pada sharing knowledge dan sosialisasi pemasaran digital. Tahap analisis situasi melibatkan kunjungan ke lokasi untuk memahami proses bisnis. Sosialisasi dan diskusi dilakukan dengan menyajikan konten tentang tren bisnis, pemasaran digital, dan strategi media sosial. Tindak lanjut mencakup anjuran untuk membuat akun media sosial tambahan dan mengoptimalkan keberadaan online. Monitoring dan evaluasi dilakukan untuk mengukur pemahaman dan penerapan praktik pemasaran digital serta memantau peningkatan penjualan melalui media sosial. Pada 10 Desember 2023 diadakan Kegiatan Pengabdian Masyarakat yang berlokasi di Mandala Wahyu Coffee Shop, melibatkan lima peserta dan tiga tahap, yakni diskusi, pelatihan digital branding dan marketing, serta evaluasi. Pelatihan ini bertujuan meningkatkan keberadaan online dan daya saing global coffee shop tersebut. Diharapkan strategi digital marketing yang diterapkan akan membuat operasional lebih efisien, mempromosikan perusahaan secara efektif, dan meningkatkan keterlibatan pelanggan. Hasil dari kegiatan pengabdian masyarakat ini adalah dilakukan upaya peningkatan penjualan dan pengembangan bisnis UMKM Mandala Wahyu Coffee Shop melalui optimalisasi digital marketing melalui media sosial. Metode melibatkan analisis situasi, sosialisasi, tindak lanjut, dan monitoring. Strategi promotion mix diharapkan efektif dalam membuat aktivitas operasional dan pemasaran digital lebih efisien. Dengan strategi digital baru, UMKM dapat menghemat waktu dan lebih efektif dalam promosi.